Regionale Arbeitsmärkte unter Transformationsdruck – unterschiedliche Herausforderungen und Anpassungspotenziale - Anette Haas; Annekatrin Niebuhr; Niklas Vetterer (Wirtschaftsdienst, 2024)
– The transformation pressure caused by digitalisation, decarbonisation and demographic change differs between regional labour markets, as does the potential to adapt to these changes. For structurally weak (rural) regions, high transformation pressure due to digitalisation and/or decarbonisation is often accompanied by significant demographic problems. Policies should aim to increase innovation and further training in lagging regions, as these are of strategic importance for addressing the challenges of transformation.
Keywords: J08; J20; J24; 330; Regionaler Arbeitsmarkt; Deutschland; Regionaler Arbeitsmarkt; Deutschland